Glass Chromatography Application: TLC Separation of Benzoic Esters in Pharmaceutical Products - Loai Aljerf; Kelli Beasley; Burton Smith; Nathan Ganeshan (International Journal of Biochemistry Advances, 2017)
p-hydroxybenzoic acid esters are used as food and drug preservatives. These compounds were quantised by a reversed-phase thin-layer chromatography method based on the use of silanized silica gel as stationary phase. Thin layers chromatography of silanized silica gel (HF254) is implemented to separate p-hydroxybenzoic acid and its methyl, ethyl, propyl, butyl and benzyl esters. Borate buffer (pH 2) was used as a mobile phase with the addition of organic solvent as required. For the quantitative determination, the solutions to be analysed were applied in bands on 5 x 20 cm plates. The plates are developed in glass chromatography chambers lined with filter paper. After the plates have been developed they are dried at room temperature. The spots or bands of the various compounds are visualised under a 250-mµ UV light source. The extraction of the silica gel with methanol was effective. Six preservatives were separated with better results for benzyl- and butyl-p-hydroxybenzoates. Chromatographic development controlled by temperature stability in the chromatographic chamber and spectrophotometric determination of all the compounds were indicated. A second development with the same solvent mixture was suggested especially when low RF is involved. Various compounds are completely separated and a good determination of p-hydroxybenzoic acid and its principle esters are possible using a simple technique of elution and spectrophotometric determination.
Keywords: Glass chromatography